6(x-1)-2(5x-4)=-10

Simple and best practice solution for 6(x-1)-2(5x-4)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-1)-2(5x-4)=-10 equation:



6(x-1)-2(5x-4)=-10
We move all terms to the left:
6(x-1)-2(5x-4)-(-10)=0
We add all the numbers together, and all the variables
6(x-1)-2(5x-4)+10=0
We multiply parentheses
6x-10x-6+8+10=0
We add all the numbers together, and all the variables
-4x+12=0
We move all terms containing x to the left, all other terms to the right
-4x=-12
x=-12/-4
x=+3

See similar equations:

| 8(8n-2)=40n+8n | | -1/4(8a+20)=-2a+5 | | 7/8=3x | | 2t-5=-10t | | 7-4(x+1)=9-5x | | 8/3=-4/3+x | | Z=-1-3i | | 4n+1=95 | | 3z/10+6=-2Z= | | 4x÷5=x+26 | | 6x+4=-22 | | 4x^2+28x-56=0 | | F(x)=4x^2–x^2,5  | | 35y+3=13y= | | 3/6x+5/10=-4/8(3x+4) | | 7n+12=1/2(12n+24) | | 2x+36=38 | | -1.4x=1 | | 4|x-5|=16 | | 100h+150=-200 | | s/10+4=2 | | 40°+(11x-18)°=180 | | 20x+15=-45 | | 18=9+3n | | 4-7=-(8n+4)+2 | | 7z/6+6=-1 | | 18=9=3n | | 2r+17=25 | | -8/3×x=9 | | 5x-27+8x-26=90 | | 1/3=5/12x=3/4 | | 19k-56/35+8/5=0 |

Equations solver categories